Trafic routier et distances de sécurité : Le dilemme de l’agriculture en Ile-de-france - Caroline Petit (Éditions en environnement VertigO, 2009)
The application of isolation distances is the easiest response for protecting agricultural crops from diffuse pollution effects still unknown. In the 90’s, some actors in the cereal supply chains have tried to limit potential risks by producing technical guidelines, including isolation distances between major roads and fields farmed under contract. These measures were then partially abandoned in the cereal sector but appeared later on in other sectors (aromatic herbs) with notable improvements. Our study focuses on the Ile-de-France region, which presents both a large agricultural area and an important road network. Through an interdisciplinary approach, our goal is to clarify this complex situation, to understand the genesis and evolution of these distances while measuring the effects concerning risk management (in connection with various uses of the precautionary principle) both socially and technically.